Analisis Penerimaan Zakat Untuk Pendidikan Dari Baitul Mal Aceh Utara(studi kasus di Dayah darul Muarrif Al-aziziyah) - Asma Asmaul Husna (LPPM, 2021)
his study aimed to determine the effectiveness of receiving zakat for education from Baitul Mal Aceh Utara in Dayah Darul Mu'arrif Al-Aziziyyah. This study used primary data obtained by distributing questionnaires to 60 respondents selected using the Census sampling method. The data analysis method used was interactive data analysis with the Miles & Huberman model by taking steps to reduce data, present data and draw conclusions. The results showed that the acceptance of zakat for education from Baitul Mal Aceh Utara for Dayah Students at Darul Mu'arrif Al Aziziyyah was effective because the assistance received was used appropriately, such as for the cost of educating students and the assistance provided was very beneficial for students with the results of the study of 46 respondents or 76.7 % of respondents who answered that this educational assistance was very beneficial and 14 respondents or 23.3% of respondents answered that this educational assistance was beneficial.